Towards school assessment resources sharing using cloud computing platform - Mat Atar, Mat Amin; Mohd Nordin, Abdul Rahman; Abdullahi Nababa, Saidu (HIKARI Ltd., 2015)
Cloud computing becomes an important technology in developing a collaborative application model for the management and sharing of resources. This research focused on sharing of examination resources among schools. Cloud computing platform is used to implement the proposed collaborative model for examination resources sharing among schools. By using the model of software as a service (SaaS) a practical application has been designed to facilitate the management of school to manage the examination resources. The examination resources sharing mechanism is modeled by applying Multi-Person Prisoner’s dilemma technique. This technique provides an incentive mechanism that would justify and encourage users to contribute resources into the application.